AB0510 INFLIXIMAB IS AN EFFECTIVE GLUCOCORTICOID-SPARING TREATMENT FOR TAKAYASU ARTERITIS: RESULTS OF A MULTICENTER OPEN-LABEL PROSPECTIVE STUDY. (2nd June 2020) - Mertz, P.; Kleinmann, J. F.; Lambert, M.; Puéchal, X.; Martin, T.; Sibilia, J.; Arnaud, L.
Abstract : Background: Approximately half of patients with Takayasu Arteritis (TA) have glucocorticoid (GC)-dependency and require the addition of a second-line immunosuppressive treatment. Objectives: Here, we conducted a multicenter open-label prospective cohort study to assess the efficacy and safety of infliximab originator as a GC-sparing agent in TA. Methods: A temporary recommendation for use for infliximab in refractory TA was approved by the French National Drug Authorities (April 2014). Infliximab was administered to patients in case of disease activity with a NIH score ≥2 despite conventional therapy. Data regarding patient's clinical, laboratory, imaging and treatments were obtained at baseline, and at each following visit until last visit (October 2017). TA activity was evaluated according to NIH criteria and GC requirement throughout the study. Results: Twenty-three patients were enrolled, including 19 female. The median age at inclusion was 33 years (Interquartile range, IQR: 23-44 years). At baseline, 17 (74%) patients were treated with GCs, at a median dose of 10 mg/day (IQR: 0-21) of prednisone-equivalent. After a median follow-up of 36.9 months (IQR: 10-58.7), improvement of ≥1 NIH criterion of TA activity was achieved for 14/22 (64%) patients. The median GC dose was 8 mg/day (IQR: 7-10) at 6 months; 5 mg/day (IQR: 0-8) at 12 months and 0 mg/day (IQR: 0-5) at 36 months of follow-up. Overall, infliximab originator had a significant GC-sparing effect between baseline and last follow-up ( p =0.009). Conclusion: This multicenter open-label cohort study suggests that infliximab originator is an effective GC-sparing treatment for TA refractory to conventional therapy. Disclosure of Interests: None declared